Perkembangan Pakan Lobster Berkelanjutan: Tinjauan Nutrisi, Binder, dan Dampak Lingkungan - Diamahesa, Wastu Ayu; Azhar, Fariq (LPPM Universitas Mataram, 2025)
Lobster aquaculture has emerged as a strategic global sector, yet faces critical challenges in sustainable and cost-effective feed formulation. This review synthesizes findings from 15 studies (2004–2025) to analyze species-specific nutritional requirements, binder efficacy, and innovation opportunities. Lobsters require high protein (>45%) for growth (especially larvae/juveniles), with limited lipids (<10%) and moderate carbohydrates (20–35%). Nutritional imbalances reduce feed efficiency and may trigger physiological disorders. Binders like carrageenan (2–4%) and sodium alginate (3%) optimize feed stability (>4 hours) and growth performance (Panulirus argus, Homarus gammarus), while natural binders (e.g., 5% cornmeal) show inferior results. Key challenges include species-specific dietary adaptations (P. cygnus thrives on natural diets), environmental impacts of nitrogen waste, and underutilized local ingredients (e.g., shrimp waste meal). The study highlights the potential of multifunctional binders, RAS/IMTA systems, and fishery byproduct-based feeds. A holistic approach integrating precision nutrition, innovative feed technologies, and sustainable farming practices is recommended to enhance productivity and environmental sustainability. Future research should prioritize binder-microbiome interactions, standardized protocols for commercial species, and circular economy models to support Indonesia’s competitive position in global lobster markets.